In Vitro Aging and Fracture Tests on Differently Veneered Partially Stabilized Zirconia Anterior Crowns - Andreas Zenthöfer; Ali Ilani; Stefan Rues (International Journal of Dentistry)
Conclusions: Within the limitations of this laboratory study, 5Y-PSZ based anterior crowns can be a viable treatment option. Framework design, choice of the veneering ceramics and artificial aging show relevant effects on the fracture resistances. Concerted veneering ceramics should be used and partially veneering of the zirconia frameworks should be favored over full veneers.